2018
DOI: 10.1021/acs.jnatprod.8b00155
|View full text |Cite
|
Sign up to set email alerts
|

Tamarixetin Exhibits Anti-inflammatory Activity and Prevents Bacterial Sepsis by Increasing IL-10 Production

Abstract: Sepsis is a systemic inflammatory response to pathogenic infection that currently has no specific pharmaceutical interventions. Instead, antibiotics administration is considered the best available option, despite increasing drug resistance. Alternative strategies are therefore urgently required to prevent sepsis and strengthen the host immune system. One such option is tamarixetin (4'- O-methylquercetin), a naturally occurring flavonoid derivative of quercetin that protects against inflammation. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…A common feature of neonatal sepsis is the systemic induction of inflammatory mediators, which can disrupt the blood-brain barrier (BBB) and interact with the brain, thereby causing brain inflammation. Sepsis is associated with the exacerbated production of proinflammatory cytokines, such as TNF-α, IL-1, IL-6, and IL-inflammatory cytokines, such as IL-10, which attempt to restore the immunological balance (Cohen, 2002;Park et al, 2018;Schulte et al, 2013). Ours findings corroborate with these findings, we describe that LPS cause a severe neuroinflammation in hippocampus of neonates.…”
Section: Discussionsupporting
confidence: 88%
“…A common feature of neonatal sepsis is the systemic induction of inflammatory mediators, which can disrupt the blood-brain barrier (BBB) and interact with the brain, thereby causing brain inflammation. Sepsis is associated with the exacerbated production of proinflammatory cytokines, such as TNF-α, IL-1, IL-6, and IL-inflammatory cytokines, such as IL-10, which attempt to restore the immunological balance (Cohen, 2002;Park et al, 2018;Schulte et al, 2013). Ours findings corroborate with these findings, we describe that LPS cause a severe neuroinflammation in hippocampus of neonates.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, researchers have confirmed that tamarixetin has the effect of inhibiting liver cancer in PLC/PRF/5 and HepG2 cells [2]. Tamarixetin has better anti-inflammatory properties compared with quercetin during bacterial sepsis via increased interleukin (IL)-10 production [8]. This property is similar to previous research that PNIPAM nanoparticles of curcuminoids could significantly decrease levels of TNF- α and IL-1 β [12].…”
Section: Introductionsupporting
confidence: 71%
“…Interestingly, stimulation of enzyme activity of CYP3A4 was observed with tamarixetin; observed residual activity was 195% ( Table 1 ). Tamarixetin exhibits anti-inflammatory activity, and prevents bacterial sepsis by stimulating immune system and interleukin 10 production [ 62 ]. It also has anticancer properties on human leukemia cells [ 63 ].…”
Section: Resultsmentioning
confidence: 99%